ASSESSMENT OF KNOWLEDGE OF BLOOD TRANSFUSION PROTOCOLS AND COMPLIANCE AMONG NURSES WORKING IN TERTIARY CARE HOSPITALS OF RAWALPINDI: A CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
This research was conducted to determine the level of knowledge of blood transfusion protocols among Pakistani nurses and to identify gaps in knowledge to reduce blood-related errors and improve patient safety. A descriptive cross-sectional research design was employed, and the study was conducted at two hospitals in Rawalpindi, with 176 nurses selected to complete a questionnaire based on the Delphi method. The knowledge of the nurses was evaluated by using the scoring <50%, 50–74%, or 75% of the knowledge was considered as poor, moderate, or high, respectively. The results revealed that the overall level of knowledge among nurses was moderate, with 55% of areas demonstrating moderate knowledge, 5% of areas showing high knowledge, and 40% of areas reflecting low knowledge. Regression analysis also showed that, education level, working experience and field of specialization enhanced the knowledge in some aspects such as the right temperature to store the RBC (p = 0.035) and patient watching (p = 0.047). Nevertheless, knowledge was not affected by marital status and employment type. The outcomes of the study also show that there is a need for education on pretransfusion checks, monitoring and management of blood products. Thus, through such gaps, the health care institutions can contribute to the prevention of transfusion errors, and ensure that the practice is more consistent and better for the patient. This paper is significant in extending the knowledge on transfusion safety and provides a basis for action in nursing education and practice.